Quantitative interrelations of Lewis antigens in normal mucosa and transitional cell bladder carcinomas. Issue 12 (December 1991) - Limas, C
Abstract : The factors regulating the expression of the Lewis blood group related antigens in tissues have yet to be clarified. In an attempt to resolve some of the existing controversies the quantitative interrelationship of the Le(a), Le(b), X and Y antigens in normal urothelium and transitional cell carcinomas (TCC) was studied using biopsy specimens derived from 22 patients whose ABO and Lewis red blood cell phenotype was known. A quantitative scale was devised to encompass both the extent and intensity of the immunohistochemical reactivity in one numerical value (score). The expression of these four antigens in the normal urothelium followed a characteristic pattern that is related to but not identical with the red blood cell phenotype. An excess of Le(b) and Y in the urothelium correlated with the Le(a-b+) red blood cell phenotype, while a relative increase in Le(a) and X (at the expense of Le(b) and Y) was associated with the Le(a+b-) red blood cell phenotype. This pattern can be accounted for by the combined effects of differential gene expression and substrate availability. The quantitative comparison of the antigenic make-up of TCCs with the corresponding normal tissue phenotype shows consistent trends, suggesting that the changes associated with neoplasia derive primarily from the suppression of specific gene products and, secondarily, from altered competitive substrate utilisation.